2020
DOI: 10.1186/s13017-020-00323-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and lymphocyte characterisation during Covid-19 infection in ICU patients: an observational cohort study

Abstract: Background: Iron metabolism and immune response to SARS-CoV-2 have not been described yet in intensive care patients, although they are likely involved in Covid-19 pathogenesis. Methods: We performed an observational study during the peak of pandemic in our intensive care unit, dosing Ddimer, C-reactive protein, troponin T, lactate dehydrogenase, ferritin, serum iron, transferrin, transferrin saturation, transferrin soluble receptor, lymphocyte count and NK, CD3, CD4, CD8 and B subgroups of 31 patients during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 32 publications
(34 reference statements)
6
49
0
2
Order By: Relevance
“…Serum iron level was reported as a potential predictor of COVID-19 severity and mortality [29]. Decreased serum iron level could predict the transition of COVID-19 from mild to severe and critical illness [30,29], which was in agreement with our ndings. Zinc is one of the micronutrients that could be consumed to reduce the intensity of SARS-CoV-2 infection and perhaps lessen the respiratory tract infection through the antiviral actions [7].…”
Section: Discussionsupporting
confidence: 92%
“…Serum iron level was reported as a potential predictor of COVID-19 severity and mortality [29]. Decreased serum iron level could predict the transition of COVID-19 from mild to severe and critical illness [30,29], which was in agreement with our ndings. Zinc is one of the micronutrients that could be consumed to reduce the intensity of SARS-CoV-2 infection and perhaps lessen the respiratory tract infection through the antiviral actions [7].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the COVID-19 context, iron metabolism is clearly disrupted in SARS-CoV-2 infected patients, especially in subjects hardest hit by the disease [122], consequently anemia [123] or hyperferritinemia are typical manifestations of hospitalized COVID-19 patients. Therefore, optimal iron status may be crucial for better disease prognosis.…”
Section: Ironmentioning
confidence: 99%
“…Also, the level of iron elevated in pulmonary fibrosis and iron chelators may inhibit pulmonary fibrosis [36]. On the other hand, it has been reported that COVID-19 patients with acute respiratory distress syndrome have low serum levels of Iron and intubation them [37]. The iron concentration 24 mcg/dl was reported in an 80-year-old patient with COVID-19 [38].…”
Section: Iron (Ferrous)mentioning
confidence: 99%
“…Iron is needed for some reactions and cellular functions like RNA/DNA synthesis and repairs [10] High level of iron may increase viral infections [36], although it has reported that COVID-19 patients have low serum level of iron [37]…”
Section: Ironmentioning
confidence: 99%